Icthyofaunal diversity of different reservoirs of Purulia District, West Bengal, India - Pradhan, Ankita; Kundu, Rabindranath; Bandyopadhyay, Nachiketa (Journal of Research in Biology, 2015)
India has 19,370 reservoirs spread over 15 states with an estimated 3.15 million hectare surface area at full capacity, and this is expected to increase due to execution of various water projects in the country. Ichthyofaunal diversity of the different reservoirs of Purulia district, West Bengal was studied in between January 2014 and December 2014. Fish species available at different reservoirs of the district essentially represented the fish faunal diversity and their abundance. The study revealed that thirty seven species (37) belonging to seven orders and fifteen families were recorded in the sampling sites of reservoirs of district. In spite of natural stocks, the reservoirs are usually stocked with fingerlings of Indian major carps and exotic carps. The order Cypriniformes was the most dominant group with 16 species, followed by Perciformes (7species), Siluriformes (6species) and, Channiformes (3 species), Osteoglossiformes and Synbranchiformes (each of 2 species), and Anguilliformes (1 species). Regarding their conservation status, 26 species were of least concern, 1 species was vulnerable, 6 species were near threatened, 1 species was data deficient, and 4 species were not evaluated (IUCN-Version 2014.1). Economical values and their seasonal abundance have also been evaluated. It was concluded that fish species gradually declining in the different Reservoirs of district due to habitat degradation, siltation, and lack of proper management practices and over exploitation could influence the percentage of fish abundance in these reservoirs.